Analisis faktor-faktor yang mempengaruhi tingkat kriminalitas pada kabupaten/kota di Provinsi Jambi (suatu pendekatan ekonomi) - Priscilla Dwi Aranthya; Purwaka Hari Prihanto; Parmadi Parmadi (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2018)
This research aims to analyze the condition and development of GDP per province of per capita, income inequality, the level of open unemployment and education in regencies / cities in Jambi Province. In addition, it also analyzes the influence of GDP per province of per capita, income inequality, open unemployment and education in regencies/ cities in Jambi Province in 2013-2017. The method of analysis in this research is panel data analysis with the fixed effect method. The research concludes that GDP per province of per capita Jambi province constantly increasing. The Gini ratio in Jambi Province varies. The open unemployment rate in Jambi Province has decreased. The average length of school in Jambi province constantly increasing. GDP per province of per capita has a positive and insignificant effect. Gini Ratio has a negative and insignificant effect. The Open Unemployment Rate has a positive and significant effect. Average School Duration has a negative and significant effect.